2019
DOI: 10.1016/j.gore.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring substance use disorder: The impact on treatment adherence in women with locally advanced cervical cancer

Abstract: The purpose of this study was to identify the prevalence of substance use disorder and its association with adherence to treatment and survival in locally advanced cervical cancer patients treated with primary radiation therapy. This is a retrospective case series of locally advanced cervical cancer patients with substance use disorder in a single academic institution treated with radiation therapy between 2005 and 2016. Substance use disorder was identified through chart review. Those with substance use disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A retrospective study among women with co-occurring SUD and locally advanced cervical cancer who were undergoing primary radiation therapy found that SUD was not associated with a difference in toxicity or survival outcomes. 7 However, other research suggests that SUD may be associated with an increase in all-cause mortality as well as other adverse outcomes for patients and health care systems (eg, emergency department visits, hospitalizations). 8 A retrospective study of patients with a history of SUD and nonsmall cell lung cancer showed that these patients had higher rates of depression, less family support, increased rates of missed appointments, more emergency department visits and more hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study among women with co-occurring SUD and locally advanced cervical cancer who were undergoing primary radiation therapy found that SUD was not associated with a difference in toxicity or survival outcomes. 7 However, other research suggests that SUD may be associated with an increase in all-cause mortality as well as other adverse outcomes for patients and health care systems (eg, emergency department visits, hospitalizations). 8 A retrospective study of patients with a history of SUD and nonsmall cell lung cancer showed that these patients had higher rates of depression, less family support, increased rates of missed appointments, more emergency department visits and more hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of studies developed with women with CC focus on the diagnostic and treatment phases (Basu et al, 2018;Rubinsak et al, 2019;SPG, 2016), this study aims to fulfill the gap regarding the follow-up phase. Therefore, the purpose of this study was to contribute to a better understanding of the CC disease trajectory, after the completion of treatments.…”
Section: Introductionmentioning
confidence: 99%